Materials based on biodegradable polymers chitosan/gelatin: a review of potential applications - Yarahmadi, Aref; Dousti, Behrooz; Karami-Khorramabadi, Mahdi; Afkhami, Hamed (Frontiers in Bioengineering and Biotechnology, 2024)
Increased mass manufacturing and the pervasive use of plastics in many facets of daily life have had detrimental effects on the environment. As a result, these worries heighten the possibility of climate change due to the carbon dioxide emissions from burning conventional, non-biodegradable polymers. Accordingly, biodegradable gelatin and chitosan polymers are being created as a sustainable substitute for non-biodegradable polymeric materials in various applications. Chitosan is the only naturally occurring cationic alkaline polysaccharide, a wellknown edible polymer derived from chitin. The biological activities of chitosan, such as its antioxidant, anticancer, and antimicrobial qualities, have recently piqued the interest of researchers. Similarly, gelatin is a naturally occurring polymer derived from the hydrolytic breakdown of collagen protein and offers various medicinal advantages owing to its unique amino acid composition. In this review, we present an overview of recent studies focusing on applying chitosan and gelatin polymers in various fields. These include using gelatin and chitosan as food packaging, antioxidants and antimicrobial properties, properties encapsulating biologically active substances, tissue engineering, microencapsulation technology, water treatment, and drug delivery. This review emphasizes the significance of investigating sustainable options for non-biodegradable plastics. It showcases the diverse uses of gelatin and chitosan polymers in tackling environmental issues and driving progress across different industries.